A Novel Small Molecule Neurotrophin-3 Analogue Promotes Inner Ear Neurite Outgrowth and Synaptogenesis In vitro - Kempfle, Judith S.; Duro, Marlon V.; Zhang, Andrea; Amador, Carolina D.; Kuang, Richard; Lu, Ryan; Kashemirov, Boris A.; Edge, Albert S.; McKenna, Charles E.; Jung, David H. (Frontiers in Cellular Neuroscience, 2021)
Sensorineural hearing loss is irreversible and is associated with loss of spiral ganglion neurons (SGNs) and sensory hair cells within the inner ear. Improving spiral ganglion neuron (SGN) survival, neurite outgrowth, and synaptogenesis could lead to significant gains for hearing-impaired patients. There has therefore been intense interest in the use of neurotrophic factors in the inner ear to promote both survival of SGNs and re-wiring of sensory hair cells by surviving SGNs. Neurotrophin-3 (NT-3) and brain-derived neurotrophic factor (BDNF) represent the primary neurotrophins in the inner ear during development and throughout adulthood, and have demonstrated potential for SGN survival and neurite outgrowth. We have pioneered a hybrid molecule approach to maximize SGN stimulation in vivo, in which small molecule analogues of neurotrophins are linked to bisphosphonates, which in turn bind to cochlear bone. We have previously shown that a small molecule BDNF analogue coupled to risedronate binds to bone matrix and promotes SGN neurite outgrowth and synaptogenesis in vitro. Because NT-3 has been shown in a variety of contexts to have greater regenerative capacity in the cochlea than BDNF, we sought to develop a similar approach for NT-3. 1Aa is a small molecule analogue of NT-3 that has been shown to activate cells through TrkC, the NT-3 receptor, although its activity on SGNs has not previously been described. Herein we describe the design and synthesis of 1Aa and a covalent conjugate of 1Aa with risedronate, Ris-1Aa. We demonstrate that both 1Aa and Ris-1Aa stimulate neurite outgrowth in SGN cultures at a significantly higher level compared to controls. Ris-1Aa maintained its neurotrophic activity when bound to hydroxyapatite, the primary mineral component of bone. Both 1Aa and Ris-1Aa promote significant synaptic regeneration in cochlear explant cultures, and both 1Aa and Ris-1Aa appear to act largely through TrkC. Our results provide the first evidence that a small molecule analogue of NT-3 can stimulate SGNs and promote regeneration of synapses between SGNs and inner hair cells. Our findings support the promise of hydroxyapatite-targeting bisphosphonate conjugation as a novel strategy to deliver neurotrophic agents to SGNs encased within cochlear bone.